The adhesion of alumina films to metallic alloys and coatings [Die haftung von aluminiumoxidfilmen auf metallischen legierungen und beschichtungen] - (:unkn) unknown (My University, 2000)
An experimental study showed that a variety of factors affect the adherence of Al2O3 scales to Fe- and Ni-base alloys. Sulfur, contained in the alloy at low levels or introduced from the exposure environment, was generally detrimental to adherence. Reactive elements improved adherence, however, yttrium was universally beneficial whereas Hf and Ti were effective in some cases and not in others. Water vapor in the exposure environment accelerated scale spallation from alloys with marginal adherence but had no effect on alloys with very adherent Al2O3 scales. The effects of sulfur, reactive elements, and water vapor all appeared to result, to first order, from effects on fracture toughness of the Al2O3/alloy interface in that they did not have a major influence on scale growth rate or residual stress in the scale, i.e. they did not have a large effect on stored elastic energy. Sulfur segregated to intact Al2O3/alloy interfaces and degraded the bond strength. Measured fracture energies are higher for artificial than for growing interfaces.